Riqueza y abundancia de mariposas diurnas, escarabajos coprófagos y plantas en cultivos orgánicos y convencionales de tres regiones de Costa Rica - Sánchez, Natalie V. (2013)
One of the main causes of biodiversity loss is related to agriculture increase and the use of chemicals. Organic farming has been proposed as a solution to biodiversity loss, for that reason we evaluated the species richness, abundance and composition of diurnal butterflies, dung beetles, herbs and trees in three different agroecosystems during 2009-2010 in Costa Rica. Organic and non-organic coffee shade (San José), vegetables (Alajuela) and Cocoa-banana farms (Talamanca) were selected to make comparisons of these biological groups. In each farm we established three transects to capture butterflies, 20 pitfall traps to capture beetles, two plots to count trees and two sub-plots to count herbs. The Cocoa-banana organic crops had higher species richness of butterflies and higher mean abundance than coffee shade and cocoa-banana crops. We detected a greatest abundance of beetles in organic farms of shade coffee and cocoa-banana. In the vegetable and cocoa-banana crops there was more abundance of herbs. Organic cocoa-banana had more trees species and they are more abundant than in conventional crops. Butterflies, herbs and trees were less similar in species composition between organic and non-organic crops; however beetles were more similar between systems. Organic shade coffee and cocoa-banana are providing a more diverse habitat and resources to butterflies than vegetables farms. The more complex plant structure, the shaded habitats and mammals present in shade coffee and cocoa-banana organic farms favor beetle abundance. In addition, beetles could be adapted to altered ecosystems. Organic farms can play an important role in butterfly and beetles conservation in countryside areas, and its benefits are influenced by forest presence and the manner in which farmers manage their land.KEY WORDSDung beetles, butterflies, organic agriculture, cocoa plantation, shade-grown coffee